The EFL Teachers' Perspective on the Implementation of Problem-Based Learning During the Pandemic Era - Sri Kurniawati (Institut Agama Islam Negeri Kerinci, 2022)
The COVID-19 pandemic shocked education systems in Indonesia. After ten months of online learning, the government stated that starting July 2021 was the beginning of a trial meeting face-to-face in the school. To meet the needs of students, the Problem-based Learning model is a suitable learning model that can improve students’ thinking skills. This study aimed to discover EFL teachers' perspectives on implementing Problem-based Learning during the Pandemic era. This research employed the descriptive qualitative research design. An interview was used to collect the data from participants 2 teachers English in a Vocational High School. The results showed that the respondents of this study had the same and different perspectives on implementing Problem-based Learning. However, the implementation has several obstacles, including low student motivation, declining student abilities, and gaps in students' ability from one group to another. The main suggestion is to apply this method in learning English as a foreign language.